Our Wild Companions: Domestic cats in the Anthropocene. (June 2020) - Crowley, Sarah L.; Cecchetti, Martina; McDonald, Robbie A.
Abstract : Cats share a long history with humans but are remarkable among domesticated species in largely retaining behavioural and reproductive independence from people. In many societies, the cat maintains liminal status as both a domestic and a wild animal. An adaptive push-and-pull between wild and domestic traits corresponds with dual roles as companions and pest controllers, and with conflicted treatment in husbandry, management, law, and public discourse. To move forward, we must proceed by understanding that cats are not exclusively pets or pests, but both a central component of human societies and an important, often adverse, influence on ecosystems. Developing a collaborative 'companion animal ecology', in which human–animal domestic relations link to ecological processes, will enable sustainable management of this wild companionship. Highlights: Cats are among the most popular companion species in the world, yet there is growing evidence of the environmental impacts wrought by their large populations. The history of their domestication and association with human societies has been effectively traced with archaeological and genetic studies of contemporary and ancient DNA. We assert that the growing conflict over cat management is underpinned by an adaptive push-and-pull between the wild and the domesticated traits of cats, aligning with their dual societal roles as companions and pest controllers. Sustainable solutions require a novel 'companion animal ecology' and recognition that cats are not exclusively pets or pests, but are central to human societies, while having important, often adverse, environmental impacts.